English-Indonesian Code Switching and Code Mixing on Students’ Bulletin Board - Hety Rochayati; Nurhaedah Gailea (Journal of English Language Teaching and Cultural Studies, 2021)
At school, where English becomes one of the subject to be learnt by students, also affected them in speaking and writing performances. They prefer to mix local languages, Indonesian Language, and English in their communication in order to be understood easily. Code switching and code-mixing often encountered in both the spoken and written language among students. It can be seen from the many writings in the bulletin board of students/wall magazine which used the code switching and code-mixing or over the code with foreign languages (English) or vernaculars. The purposes of study are to describe the forms and the reasons of code mixing and code switching used in students’ bulletin boards. The case study method was used in this work. The results show that the most frequent type of code switching used by the students is intra-sentential switching (56 %), inter-sentential switching is in the second place (32%), and the last is tag switching (12%). The most frequent type of code mixing used by the students is insertion (word or phrase) (63.94%), the lexicalization (dialect) is in the second place (26.22%), and the last is alternation (clause) (9.84 %). Students prefer to talk in one language rather than in another, and they feel free and more comfortable to express their emotional feelings in a language that is not his/her everyday language. A bulletin board is one where students have an opportunity to interact with manipulatives themselves. Code switching and mixing build prestige because through this way the editor staff will look more educated. Showing group identity is another reason of the use of code switching and code mixing. The last is, the most common reason for bilingual/multilingual person to switch  or  mix  their languages is due to the lack  of  equivalent  lexicon  in  the  languages.